Contribution of Individual, Community, and Health System Factors to Health Outcomes in Inner-city African Americans with Type 2 Diabetes - (:unkn) unknown (My University, 2020)
Diabetes is a complex disease that represents a major public health challenge due to its high prevalence, its association with increased morbidity, and early mortality. Inner-city African Americans with diabetes suffer a disproportionate burden of disease due to both economic and social disadvantage that reaches across individual, community, and health system levels of influence. Central to the principles of Public Health is the “pursuit of health equity for the elimination of health disparities, specifically in accordance to the empowerment of disenfranchised community members, aiming to ensure that the basic resources and conditions necessary for health are accessible to all”. To effectively achieve health equity in diabetes for inner-city African Americans and provide the basic resources and conditions necessary for health; establishment of barriers specific to diabetes care is paramount. The current study addresses several gaps in the literature for inner-city African Americans with diabetes by first developing a framework for understanding barriers to diabetes care for inner-city African Americans that occur across multiple levels of influence. Specifically, this framework integrated two existing behavioral models for diabetes and was informed by the literature and a social ecological model for health disparities to identify barriers at the individual, community, and health system level. Using the newly developed framework, this study then examined the influence of each barrier level on two important diabetes outcomes, glycemic control and quality of life, among inner-city African Americans with diabetes. Primary data from 241 inner-city African Americans with diabetes were analyzed. Hemoglobin A1C (A1C) was collected for each participant and served as the measure of glycemic control. The SF-12 was used to capture the physical component (PCS) and mental component (MCS) of quality of life. Advanced regression methods using four approaches including sequential, stepwise with backward and forward selection, and all possible subsets regression, were used to identify factors that may be key drivers of outcomes for inner-city African Americans with diabetes. The findings showed that factors across the three levels of influence: individual, community, and health system, have a differential relationship with glycemic control and quality of life. For glycemic control, in the final adjusted model across all four approaches, individual level factors like age (-0.05; p For quality of life, in the final adjusted models, having less than a high school education (-0.78; p=0.006), and having major depression (-1.51; p This study serves as preliminary for understanding barriers unique to inner-city African Americans and identifying important factors that may be driving glycemic control and quality of life. Future steps need to examine the indirect pathways that may exist within this framework contributing to poor outcomes. Additionally, application of this framework for intervention development may allow for the development of tailored and specific interventions that promote health equity and improve outcomes in diabetes for inner-city African Americans.
Keywords: African American; Diabetes; Inner City; Multilevel Factors